Association of food insecurity and sleep difficulty among 189,619 school-going adolescents: a study from the global in-school students survey - Osei Bonsu, Emmanuel; Afetor, Maxwell; Munkaila, Lambongang; Okwei, Reforce; Nachibi, Stephen Uwumbordo; Adjei, Benjamin Noble; Frimpong, Eric; Arimiyaw, Abdul Wahid; Adu, Collins; Peprah, Prince (Frontiers in Public Health, 2023)
Introduction Adolescents' sleep disturbances are associated with chronic and dramatic physical, emotional, and mental development and school performance consequences. Although food insecurity could significantly contribute to these effects, few studies have explored the effect of food insecurity on sleep disturbances among adolescents. The study aimed to examine the relationship between adolescents' food insecurity and sleep disturbance. Methods Data on 189,619 adolescents were drawn from the cross-sectional global adolescent health surveys conducted between 2015 and 2018 in 35 countries and territories. Univariate and multivariable multinomial regression models were fitted to examine the hypothesized associations. Results Overall pooled prevalence of moderate (45.2% (95%CI=43-47)) and severe (5.8% (95%CI=5-6)) food insecurity levels were reported. About (52.6% (95%CI=51-54)) moderate and (8.6% (95%CI=8-9)) severe worry-induced sleep disturbances were found. Considering the fully adjusted multinomial logistic model, moderate food insecurity was significantly associated with moderate (AOR= 1.70 CI=1.59-1.81; p<.0001) and severe (AOR= 1.63 CI=1.42-1.87; p<.0001) sleep disturbances. Also, adolescents reporting severe levels of food insecurity had moderate (AOR=1.88 CI=1.68-2.11; p<.0001) and severe (AOR=4.07 CI=4.74-6.11; p<.0001) sleep disturbances. Females and those aged between 15-17 years and 18 or more were at higher risk of moderate and severe sleep disturbances in the context of food insecurity. Conclusion Reducing food insecurity could be an effective policy strategy for enhancing adolescent sleep quality.